Hand-Speaking Technology: An Expert and User-Based Assessment of the VLibrasWidget - Macêdo, Thaís Melquíades; Germano, Vinícius; Costa, Carolina de Melo; Aguiar, Yuska Paola Costa (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2025)
The use of assistive technology to support the inclusion of deaf individuals in the digital environment is a valuable resource when it becomes necessary to scale the translation services typically provided by human interpreters. VLibrasWidget is an open-source computational solution designed to translate digital content (text, audio, and video) into Brazilian Sign Language (Libras) through animation. This tool is available on more than 120,000 websites, with an average of 100,000 translations per day. Given the widespread use and social impact of VLibrasWidget, it is important to consider that usability and accessibility aspects are essential for its effective use. Therefore, this experience report presents the planning, execution, and results of an evaluation of VLibrasWidget, combining a heuristic usability review by experts with user testing involving both deaf and hearing participants—through usage observation and subjective satisfaction probing. The complementary results enabled the identification of 28 interface and interaction issues with varying severity levels (1 high; 8 medium; 10 low; 9 cosmetic), indicating that the tool has room to evolve in order to better serve its users.